Pullulan/Poly(2-Hydroxyl Ethyl Methacrylate) Cryogels - Ustürk, Selma (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Pullulan – polyHEMA cryogel systems were synthesized by using radical chain polymerisation with the aid of chemical crosslinkers. Pullulan- ECH-graftpolyHEMA cryogels and pullulan-ECH-graft-polyHEMA-EGDMA cryogels were prepared from various different concentrations of starting monomer; 2-hydroxy ethyl methacrylate (HEMA) and natural polymer; pullulan. For all the cryogel systems epichlorohydrin (EPC) was used as crosslinker and for some of them in addition to EPC , ethylene glycol dimethacrylate was used. For the initiation of polymerization, the redox couples of ammonium persulfate (APS) and N,N,N’,N;-tetramethelen diamine (TEMED) were used. Swelling characteristics of the cryogel systems were analysed in three different conditions; acidic, neutral and basic conditions at 25 ℃. The concentrations of monomers and crosslinkers were altered to synthesize different cryogels with different swelling characteristic features. In addition, scanning electron microscopy (SEM) and FT-IR spectroscopy analyses were used for structural and morphological characteristic features determination. Based on dynamic swelling tests, it was found that pullulan-ECH-graft-polyHEMA-EGDMA cryogels bears the highest equilibrium swelling capacity characteristics with 97 %. These cryogels has got the highest degree of porosity among all the other types of cryogels. Keywords: Pullulan- ECH-graft-polyHEMA cryogels, epichlorohydrin (EPC), ammonium persulfate (APS) and N,N,N’,N;-tetramethelen diamine (TEMED).

ÖZ: Pululan – polyHEMA kriyojel sistemleri serbest radikal zincir polimerizasyonu ve çapraz bağlayıcı varlığında sentezlenmiştir. Monomer olarak 2-hidroxy etil metakrilat (HEMA) ve doğal bir polimer olan pululan kullanılarak değişik konsantrasyonlarda pullulan-ECH-graft-polyHEMA kriyojeller ve pululan-ECHgraft- polyHEMA-EGDMA kriyojeller hazırlanmıştır. Tüm kriyojel sistemleri için çapraz bağlayıcı olarak epiklorohidrin ve epiklorohidrinin yanında etilen glikol dimetakrilat da (EGDMA) kullanılmıştır. Polymerizasyon başlatıcı çifti olarak amonyum persülfat (APS) ve N,N,N’,N;-tetramethilendiamin (TEMED) kullanılmıştır. Kriyojellerin karakterizasyonu için 25 ℃ de saf su içinde , asitli ve bazik sulu ortamda yürütülen dinamik şişme çalışmaları gerçekleştirilmiştir. Deneylerde monomer ve çapraz bağlayıcı miktarı değiştirilerek farklı şişme özelliği gösteren kriyojeller sentezlenmiştir. Bunun yanı sıra, yapısal ve morfolojik karakterizasyon için taramalı elektron mikroskobu (SEM) görüntüleri alınmış ve FT-IR analizleri yapılmıştır. Dinamik şişme çalışmaları sonucunda, en uygun şişme profili gösteren kriyojel sisteminin %97 denge su içeriği ile pullulan-ECH-graft-polyHEMA-EGDMA kryojelleri olduğu görülmüştür. SEM görüntülerinde ise en yüksek miktarda por sayısı yine aynı tür kriyojel sistemlerinde gözlemlenmiştir. Anahtar kelimler: pullulan-ECH-graft-polyHEMA kriyojeller, epiklorohidrin (EPC), amonyum persülfat (APS) ve N,N,N’,N;-tetramethilendiamin (TEMED).
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2019. Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Chemistry; Polymers; Pullulan- ECH-graft-polyHEMA cryogels; epichlorohydrin (EPC); ammonium persulfate (APS) and N,N,N’,N;-tetramethelen diamine (TEMED)